A method to evaluate the functional state of the human brain after acute in-hospital stroke - K. S. Brazovskii; D. A. Vinokurova; V. A. Strezh; V. Yu. Ussov (Бюллетень сибирской медицины)
Acute in-hospital stroke is a severe complication of the early recovery period after cardiovascular surgery with a probability of up to 15%. Unfortunately, in-time diagnostic neuroimaging (computed tomography and magnetic resonance imaging) in cases of severe brain damages is considerably hindered increasing the risk of an adverse outcome.The aim of the study was to develop a method to evaluate the functional state of the human brain in patients with severe in-hospital stroke measuring parameters of electrical activity in the central nervous system.Materials and methods. The sample was composed of 20 anonymous archived electroencephalograms obtained from volunteers with no neurological disorders, 10 records of patients without neurological symptoms during general anesthesia, 17 records of patients with out-of-hospital strokes obtained from the UCLH Stroke EIT Dataset, and 18 records from patients with acute in-hospital stroke during neuromonitoring in the early postoperative recovery period. A new integral coefficient of the functional state was introduced, and an algorithm to calculate the proposed measure of the functional activity of the central nervous system was developed and implemented.Results. The proposed method to evaluate the functional state of the human brain was applied to analyze neurophysiological records obtained from people with different activity of the nervous system: from resting state to deep coma. It was shown that the integral coefficient naturally reflects the functional state of the human brain and can be used for early detection of brain dysfunction and damages caused by cerebral hemodynamic impairment.Conclusion. The introduced integral criterion to evaluate the functional state of the human brain can be used for long-term postoperative monitoring in cardiac patients who underwent surgical treatment.